Mengapa Masyarakat Memilih Menunaikan Zakat di Masjid Dibandingkan Dengan Lembaga Zakat? (Studi Kasus Pada Masyarakat Desa Kramat Jegu Kecamatan Taman Kabupaten Sidoarjo) - Novianto, Henry Reza; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of research is to find out Why Public Choose Paying Zakat in Mosque Rather than Institute of Zakat in Kramat Jegu Village.The research methodology used was a qualitative approach, the case study strategy. Data was collected by interviewing nine muzakki zakat payers in Kramat Jegu village Taman sub-disctric who four of them are related to the management of the mosque.The technique used is descriptive analysis.The result showed that the public would prefer to pay zakat in the mosque than zakat institutions. The motivation of public to pay Zakat at mosques fortified with three reasons are take into account the distance of the place of payment of zakat, more public believe to staff management mosque of zakat, and the public awareness to help the surrounding community.